Fundamentals of machining and machine tools - Boothroyd, G. (Geoffrey) (Manufacturing engineering and materials processing, 1989)
Suitable for a college-level course in the principles of machine tools and metal machining, this textbook presents topics that include: operations, mechanics of cutting, temperature, and tool life.